Growth and photosynthetic rate of Shorea parvifolia and Shorea mecistopteryx in a rehabilitated forest. - Wong, Kok Mun; Ong , Kian Huat; King, Jie Hung (2012)
Tropical forests are fast disappearing. Available forested areas al-e inostly in degraded condition that may not be suitable for dipterocarp species to grow. Reforestation could bring back these forests. The objectives of this study were to determine the diameter growth rate and photosynthetic rate of 17-year-old Shorea pa~vlfolia and Shorea mecistopteryx established in a rehabilitated project. Although both species have similar leaf area index, diameter growth rate of S. rnecisfopferyx is higher as compared to 5'. pawijblia. Shovea mecistopteryx recorded significantly higher photosynthesis rate than S pawijblia. Pearson's Correlation Coefficient confirmed that growth rate was influenced by photosynthetic rate.